Upaya Rusia Dalam Mencapai Kepentingan Nasional Melalui Kebijakan Near Abroad Terhadap Kirgistan Pada Tahun 2000 – 2014 - Sumerta Putri, Ni Putu Metaliana; Fasisaka, Idin; Parameswari, Anak Agung Ayu Intan (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2018)
ABSTRACT Russia was the largest independent Soviet republic in 1991. In an attempt to gain Russian influence over other former Soviet Union countries, Russia focused its attention on those countries. Kyrgyzstan is one of the countries located in Central Asia, which has great potential in the military field. The emergence of the United States in Kyrgyzstan by setting up a military base since 2001, has prompted Russia to seek to eliminate the influence of the United States in Russia. To maintain the stability of the Russian hegemony in Kyrgyzstan, Russia undertakes various ways in both politics, economy and security. To maintain the stability of Russian hegemony, Russia has the most focus on military security in Kyrgyzstan. This effort is realized by providing various kinds of military assistance and facilities to Kyrgyzstan. Keywords: Russia, Kyrgyzstan, USA, Hegemony Stability, Military Security